Rb1, the Primary Active Ingredient in Panax ginseng C.A. Meyer, Exerts Antidepressant-Like Effects via the BDNF–Trkb–CREB Pathway - Wang, Guoli; Lei, Cong; Tian, Ya; Wang, Yingping; Zhang, Lianxue; Zhang, Ronghua (Frontiers in Pharmacology, 2019)
Panax ginseng C.A. Meyer (Araliaceae), a popular tonic and dietetic herbal medicine, has been traditionally prescribed in China and other countries to treat affective disorders. The medicinal parts of ginseng, the roots and flower buds, have become increasingly popular as dietary supplements due to the current holistic healthcare trend. We have investigated for the first time the antidepressive actions of the different medicinal parts, namely, the main roots, fibrous roots, and flower buds (in water extract and powder), of garden-cultivated ginseng through behavioral and drug-induced tests in mice. The water extracts, but not the powders of ginseng fibrous roots, flower buds, and main roots (1.5 g crude drug/kg, p.o.), significantly reduced the immobility time in the forced swim test (FST) and tail suspension test (TST); moreover, the water extracts enhanced the 5-hydroxytryptophan (5-HTP)-induced head-twitch response and antagonized the action of reserpine in the mouse. We then explored the antidepressive mechanism of action of the ginsenoside Rb1 (Rb1) related to brain-derived neurotrophic factor (BDNF) and its downstream proteins in mice exposed to chronic unpredictable mild stress (CUMS). Treatment with Rb1 (20 mg/kg, p.o.) for 21 days significantly attenuated the CUMS-induced decrease in the activities of BDNF, tropomyosin-related kinase B (TrkB), protein kinase B (AKT), extracellular regulatory protein kinase (ERK), and cAMP response element binding protein (CREB) in the mouse hippocampal CA3 region and prefrontal cortex (PFC). Interestingly, treatment with the novel TrkB antagonist ANA-12 (0.5 mg/kg, i.p.) did not alter the level of BDNF, but significantly blocked the antidepressive effects of Rb1 on proteins downstream of BDNF in CUMS-treated mice. These results suggest that BDNF-TrkB-CREB signaling may be involved in the antidepressive mechanism of the action of Rb1.